Technical Guidance on Giant Gourami (Ospronemus Gouramy) Seed Production Sikonah: Bimbingan Teknis Produksi Benih Ikan Gurami (Ospronemus gouramy) Sikonah - Agussyarif Hanafie; Fatmawati; Ririen Kartika Rini; Olga; Siti Aisiah; Muhammad Fatur Rahman; Muhammad Yusuf (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Community service activities are aimed at improving the knowledge and skills of the Aquaculture Entrepreneur group in the irrigation ponds of Sungai Sipai Village, Martapura District, Banjar Regency, South Kalimantan Province. The target audience has not been able to produce quality, sustainable gourami (Ospronemus gouramy) seeds, and does not know and understand the technique of fish nursery using the earthen pond system (sikonah). The results of the activity show that the production of sikonah gourami fish seeds has been successfully implemented with high enthusiasm from the target audience. Partners also have a good understanding of all the knowledge materials provided. After the activity, there was an increase in knowledge of more than 3.44 times from the initial condition. The target audience mastered all skills after the implementation of technical guidance. There was an increase in skills of 4.49 times from the initial condition.